PENGARUH BIAYA BAURAN PROMOSI TERHADAP VOLUME PENJUALAN ROKOK SAMPOERNA A-MILD DI KOTA PADANG - Rahmat Ihsan, Rizki; Natassia, Rizky; Jolianis, Jolianis (Pendidikan Ekonomi, 2014)
Â ABSTRACTSales activity is an activity that should be done by the company to market its products in the form of goods or services. Turnover activities undertaken by the company aims to achieve the expected sales volume and favorable to achieve maximum profit for the company by way of sale to the consumer. Issues that are examined in this study was the effect of the cost volume of the promotional mix Sampoerna A Mild cigarette sales in the city of Padang. The purpose of this study was to analyze the effect of the advertising (X1), personal selling (X2), sales promotion (X ), and publicity (X ) against cigarette sales volume Sampoerna A Mild - desert city. Data collection techniques using the documentation, the data were analyzed with multiple linear regression method.. 246.155 Fhitung test with significant values of 0.000 < Î±= 0.05 and test the coefficient of determination (R Square) of 99 %, while the remaining 1 % is explained by other variables or causes beyond regression models of this study. Based on the results of this study concluded that the entire cost of the promotion mix such as advertising costs , the cost of personal selling , sales promotion costs and publicity costs and a significant positive effect on the volume of sales of cigarettes Sampoerna A - Mild in the city of Padang.